PENGARUH PERCEIVED VALUE DAN CUSTOMER EXPERIENCE TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI MEDIASI PADA PENGGUNA INDRIVE MAHASISWA FAKULTAS EKONOMI UNIVERSITAS NEGERI MEDAN - Checilia Sihotang, Irene; Hutasuhut, Saidun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low level of customer loyalty to the inDrive online transportation platform among price-sensitive demographic groups such as college students, a situation exacerbated by the phenomenon of multi-homing as well as systemic challenges such as uncertainty regarding negotiated fares, map inaccuracies, driver behavior, and digital payments. This study aims to analyze the influence of perceived value and customer experience on customer loyalty, with customer satisfaction as a mediating variable, among inDrive users who are students in the Faculty of Economics at the State University of Medan. The research method used was quantitative, employing a causal-associative approach. Sampling was conducted using purposive sampling, with a sample size of 130 respondents current students from the 2022–2025 cohorts who had used inDrive at least twice. Data analysis was conducted using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method via SmartPLS 4.0 software, including tests of the outer model, inner model, hypothesis testing, and mediation effect size testing using the upsilon statistic. The results of the study indicate that all instruments met the criteria for convergent validity (factor loadings > 0.7), discriminant validity (AVE > 0.5), and very high reliability (composite reliability > 0.7). The research findings indicate that perceived value is in the high category, while customer experience and customer loyalty remain in the moderate category. Structural testing has shown that perceived value and customer experience have a direct, positive, and significant impact on customer satisfaction and customer loyalty. Furthermore, customer satisfaction has been empirically shown to act as a mediating variable (partial mediation) that reinforces the influence of perceived value and customer experience in shaping long-term customer loyalty.